The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.ijcard.2011.10.133
|View full text |Cite
|
Sign up to set email alerts
|

A crossover comparison of urinary albumin excretion as a new surrogate marker for cardiovascular disease among 4 types of calcium channel blockers

Abstract: 40.6 (18.7-94.7). By all agents, significant augmentations were observed in PRA, angiotensin I and angiotensin II (AngII). AngII at cilnidipine was significantly lower than that at amlodipine. PAC at cilnidipine and efonidipine was significantly lower than that at amlodipine. Nifedipine CR significantly reduced ANP concentration. Conclusions: It is revealed that only nifedipine CR and cilnidipine could reduce albuminuria statistically. Thus, it is suggested that the 2 CCBs might be favorable for organ protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 46 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…A total of 1494 studies were identified. Among these studies, twenty-four studies [12] [35] with a total of 1,696 participants (including 809 studies assessing T-type CCBs versus L-type CCBs and 887 studies assessing T-type CCBs versus RAS antagonists) met the inclusion criteria and were selected for the statistical test (see Table 1 ). Six articles [13] , [16] , [18] , [20] , [21] , [22] lacked data regarding renal function or plasma aldosterone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 1494 studies were identified. Among these studies, twenty-four studies [12] [35] with a total of 1,696 participants (including 809 studies assessing T-type CCBs versus L-type CCBs and 887 studies assessing T-type CCBs versus RAS antagonists) met the inclusion criteria and were selected for the statistical test (see Table 1 ). Six articles [13] , [16] , [18] , [20] , [21] , [22] lacked data regarding renal function or plasma aldosterone.…”
Section: Resultsmentioning
confidence: 99%
“…However, for DBP and SCr in the T-type CCB vs. RAS groups, the I 2 value was greater than 50%; hence, the random effects model was used. The results of quality assessment for each included study indicated that eighteen reports [13] [21] , [24] [27] , [29] – [33] were high quality and that the remaining six studies [12] , [22] [23] , [28] , [34] – [35] were moderate quality (see Table 1 and Table S1 ). The overall quality of the evidence was high in our statistical tests.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When nifedipine CR was administered at night, nocturnal BP was significantly decreased [17], and U-Alb excretion may also be decreased. Second, different kinds of CCBs prevent albuminuria to different degrees [11, 12]. In fact, some reports have indicated that nifedipine CR decreased albuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some reports have indicated that nifedipine CR decreased albuminuria. Nifedipine CR and cilnidipine, but not efonidipine and amlodipine, significantly reduced albuminuria [11]. Combination therapy with standard-dose candesartan and nifedipine CR is more effective than up-titrated candesartan monotherapy for reducing BP and improving U-Alb while maintaining eGFR [12].…”
Section: Discussionmentioning
confidence: 99%